Training the vertical jump to head the ball in soccer - Paoli, A.; Bianco, A.; Palma, A.; Marcolin, G. (Strength and Conditioning Journal, 2012)
In modern soccer, heading the ball is both an offensive tool used to score goals and a defensive measure against opposing teams. Proficiency in heading the ball requires proper technique in conjunction with an effective vertical jump. The aim of this article is to address the factors involved in vertical jump performance and how they relate specifically to heading the ball.